2022
DOI: 10.3389/fimmu.2022.913901
|View full text |Cite
|
Sign up to set email alerts
|

Innate/Inflammatory Bioregulation of Surfactant Protein D Alleviates Rat Osteoarthritis by Inhibiting Toll-Like Receptor 4 Signaling

Abstract: Osteoarthritis (OA) is a deteriorating disease of cartilage tissues mainly characterized as low-grade inflammation of the joint. Innate immune molecule surfactant protein D (SP-D) is a member of collectin family of collagenous Ca2+-dependent defense lectins and plays a vital role in the inflammatory and innate immune responses. The present study investigated the SP-D-mediated innate/inflammatory bioregulation in OA and explored the underlying molecular mechanism. Transcriptome analysis revealed that SP-D regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…Macrophages proliferate excessively and are abnormally recruited locally to joints during OA development. [ 34 ] In this study, a CCK‐8 assay and Edu staining were used to measure the proliferation of RAW 264.7 treated with different hydrogel groups. The results showed no significant differences in cell proliferation among the LPS, blank NPs@HPCH, O 2 NPs@HPCH, O 3 NPs@HPCH, and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages proliferate excessively and are abnormally recruited locally to joints during OA development. [ 34 ] In this study, a CCK‐8 assay and Edu staining were used to measure the proliferation of RAW 264.7 treated with different hydrogel groups. The results showed no significant differences in cell proliferation among the LPS, blank NPs@HPCH, O 2 NPs@HPCH, O 3 NPs@HPCH, and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this study regarding the protective effect of Resatorvid in an experimental inflammatory TMJOA model have not been documented but have been reported in knee OA and rheumatoid arthritis (RA) pathogenesis. Jiang’s study verified that administration of Resatorvid suppressed cartilage degeneration and inflammatory and immune responses in a rat OA model [ 30 ]. Samarpita et al confirmed that Resatorvid significantly reversed the body weight and paw thickness of adjuvant-induced arthritis (AIA) rats to the normal state, reduced the increased serum inflammatory factor levels, and ameliorated joint inflammatory symptoms [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown the critical role of the NF‐κB pathway in M1 polarization and subsequently inflammatory cytokine release, such as IL‐1β, IL‐6 and TNF‐α 70,71 . In OA, when PAMPs from microorganisms or DAMPs from damaged tissue are released, the activation of Toll‐like receptors (TLRs) leads to the M1 polarization, which is regulated via the TLR/NF‐κB signaling pathway 72 . This implies that the block of TLRs might be a potential target for not only M1 polarization but also a promising OA therapy.…”
Section: Signaling Pathways In Macrophage Polarizationmentioning
confidence: 99%
“… 70 , 71 In OA, when PAMPs from microorganisms or DAMPs from damaged tissue are released, the activation of Toll‐like receptors (TLRs) leads to the M1 polarization, which is regulated via the TLR/NF‐κB signaling pathway. 72 This implies that the block of TLRs might be a potential target for not only M1 polarization but also a promising OA therapy. Berberine was found to inhibit M1 polarization through a block of the TLR4/MyD88/NF‐κB signaling pathway and attenuate inflammation in the early phase.…”
Section: Signaling Pathways In Macrophage Polarizationmentioning
confidence: 99%